Image Processing an Emerging Technique for Early Detection of Pest and Diseases - Kandiah, P (Agriculture Observer, 2021)
Agriculture is a prime and foremost important sector for almost all developing countries. Agriculture production is hindered and declined by the pest and diseases which imposes a threat to food security. Therefore, it becomes necessary to fast and accurate early detection and diagnosis of the pest and diseases to safeguard crops from enormous yield losses. Conventional pest detection and diagnosis are time-consuming, and relied on plant protection experts. Recent advances in information and communication systems opened digital agriculture, and pests and diseases are quickly detected and diagnosed using newly emerging technology call “image processing”. This article attempts to enlighten the advanced technological knowledge of image processing, and its success in the detection of economically important crop pests and diseases around the world